Pengembangan Instrumen Asesmen Praktik Lapangan Berbasis Outcome-Based Education - Febriani, Ayu Rizky; Hidayat, Rohman; Anggraeni, Dewi (Jurnal MensSana, 2025)
Assessment in field practice learning within higher education Physical Education programs continues to face challenges in measuring learning outcomes comprehensively and objectively, particularly across psychomotor, cognitive, and affective domains. This study aimed to develop a Field Practice Learning Assessment Instrument (ASPRAK) that is valid, feasible, and effective for use in outcome-based practical learning. The study employed a Research and Development (R&D) approach using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The research subjects included course instructors and undergraduate students enrolled in field practice courses in the Physical Education program. Data were collected through expert validation and small-scale and large-scale trials using Likert-scale questionnaires. Data analysis was conducted using descriptive quantitative techniques by converting scores into feasibility percentages. The results indicated that the ASPRAK instrument achieved an average feasibility score of 82%, categorized as feasible, and demonstrated high alignment with Course Learning Outcomes and sub-learning outcomes, ease of independent use, and strong support for student self-reflection. Therefore, ASPRAK has the potential to serve as an objective, transparent, and applicable assessment instrument to support the implementation of Outcome-Based Education in field practice learning in higher education. Keywords: learning assessment, field practice, physical education, Outcome-Based Education, ADDIE